(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The stratigraphic expression and geological significance of the contact between the Vinchina (Late Miocene) and Toro Negro (Late Miocene-Pliocene) formations (Turner, 1964; Ciccioli et al., 2010) is analyzed in this paper. These units with more than 8,000 m of sediments (Ramos, 1970; Tripaldi et al., 2001; Ciccioli, 2008) represent the main units of the infill of the Vinchina Basin (Ciccioli et al., 2010) (Figs. 1-3) during the transition from a simple foreland basin stage to a broken foreland one (Ciccioli, 2008; Ciccioli, et al., in press). They mostly represent sedimentation by fluvial and aeolian processes in an inland basin during an overall warm and dry climate period (Tripaldi et al., 2001; Ciccioli, 2008). Thus, major changes in sedimentation are thought to correspond with tectonic events (Ciccioli et al., in press). The lower member of the Vinchina Formation and the upper member of the Toro Negro Formation present a more uniform and extended sedimentation pattern. In contrast, the upper member of the Vinchina Formation and the lower member of the overlying Toro Negro Formation show important lateral (north-south) facies changes (Fig. 4). The along-strike differences in the character of the discontinuity marking the boundary between the Vinchina and Toro Negro formations, is the most meaningful of them all. Six sections, from north to south (La Aguada creek, Los Pozuelos creek, north La Troya river, south La Troya river, Campo Negro and del Yeso creek) were measured across the boundary between the Vinchina and Toro Negro formations along the Sierra de Los Colorados (Fig. 2). Facies associations within this interval were defined and sedimentary paleoenvironments interpreted. The information gathered from these sections allowed interpreting the contact between the Vinchina and Toro Negro formations as a high-relief incision surface that in some places suppresses up to 25% of the underlying Vinchina Formation (Figs. 4 and 5). This surface forms a west-east oriented paleovalley in the north (La Aguada and Los Pozuelos sections), is a low-relief incision surface (showing minimum stratigraphic suppression) in the central part of the study area (south La Troya river and Campo Negro sections) and becomes in a non-erosive planar surface at the southern end (del Yeso creek, Figs. 6 and 7). Considering the available radiometric data (Ciccioli et al., 2010), the age of the unconformity can be bracketed between 19.1 and 8.6 Ma. Four stratigraphic sections were defined in the deposits of the Toro Negro Formation overlying the incision surface (Table 2). Section S1 is composed of extraformational conglomerates, agglomerates and intraformational breccias. Coarse-grained conglomerates, gravelly sandstones and coarsegrained sandstones predominate in section S2 together with scarce mudstones and very fine-grained sandstones. Section S3 comprises coarsening-upward sequences composed of mudstones, sandstones and conglomerates. Finally section S4 is made up by mudstones and fine-grained sandstones with scarce levels of conglomerates and coarse-grained sandstones. Section S1 is interpreted as incision-confined fluvial deposits accumulated under low-accommodation conditions. Section S2 is also interpreted as confined to the paleovalley but with increasing accommodation space. Finally sections S3 and S4 mark the shift from confined to unconfined conditions under high accommodation. The Vinchina Formation was reported to crop out in the higher areas of the Famatina range but up to now there is no record of the Toro Negro Formation in that area. The deep, long-lived, west-east oriented paleovalley described in the northern part of the area is an atypical feature for the foreland basin model. However, the lack of a relationship with contemporaneous marine deposits and evidences of an arid climate throughout the deposition of the Vinchina and Toro Negro Formations suggest a tectonic control for the changes in the erosion vs accumulation rates in the basin. Therefore the incision and infill of the paleovalley is interpreted using the relationship between the fluvial equilibrium-profile and the channel profile (C.f. Dalrymple et al., 1998; Shanley and McCabe, 1994; Blum and Törnqvist, 2000) (Fig. 8) The meandering fluvial system interpreted from deposits of Facies Association (FA) V of the Vinchina Formation (Tripaldi et al., 2001) represents a stage of high accommodation (point A in Fig. 8). After that stage, a progressive lowering of the relative equilibrium profile reduces the accommodation the development of amalgamated channel belts of the fluvial systems interpreted for FA VII (Tripaldi et al., 2001) similar to the "unconfined stream equilibrium profile low" of Dalrymple et al. (1998).This trend continued until the equilibrium profile places below the channel profile. At that point erosion and sediment bypass took place. The major degree on incision and sediment bypass occurred at point C in figure 8 but erosion and down-cutting occurs until point E. At this latter point the equilibrium profile passes above the stream profile and aggradation begins within the incised valley ("confined stream equilibrium profile low" de Dalrymple et al., 1998). Finally, maximum accommodation (point F in figure 8) is represented by the anastomosing fluvial system with encased channels in fine-grained overbank deposits of section S4. As neither the west-east orientation of the observed paleovalley nor the evolution of the sedimentary environments can be explained by the eastward advance of the fold and thrust belt in a simple foreland basin we interpret that the uplift of the Famatina range (cf. Ramos et al., 2002; Davila and Astini, 2007; Davila, 2010) to the east of the studied area (Fig. 9) might have produced a narrow area of high subsidence modifying the stream profiles of the rivers draining from the Andes. In the distal area (Los Colorados range) stream profile dropped below the equilibrium profile causing deep incision while close to the uplifted range rapid deposition might have occurred. Therefore the incision surface separating Vinchina and Toro Negro Formations is related to the main phases of uplift of the western Famatina range (Figs. 10 y 11). This event produced accelerated subsidence and increased accommodation in the proximal area and lowering of the equilibrium fluvial profiles (and incision) in the distal areas to the west (Fig. 10b). During post-tectonic times, subsidence and accommodation rates decrease close to the uplifted area and the relative rise of the fluvial equilibrium profiles in the distal area with renewed aggradation (Fig. 10c). A model explaining the interpreted changes in accommodation relative to the subsidence due to the uplift of the Famatina is shown in figure 11.